Institutional partisanship - Walter, Aaron T. (Slovak Journal of Political Sciences, 2016)
The balance of power between the legislative and executive branches of government in the United States has held firm despite the evolution of each branch. Moreover, as the primacy of one branch succumbed to the dominance of the other there remained a constant variable. Partisanship existed since the American founding, however, the importance of Congressional partisanship in the later half of the nineteenth century and rise of the imperial presidency in the twentieth century highlight the formidable challenges of divided government in the United States. The following paper utilizes rational choice theory in political science to explain decision making of American political leaders though inclusion of casual and descriptive examples highlight certain choices within